2018
DOI: 10.1245/s10434-018-6483-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Abdominoperineal Resection for Squamous Cell Anal Cancer: A 30-Year Single-Institution Experience

Abstract: BackgroundFailure of chemoradiotherapy (CRT) for anal squamous cell carcinoma (SCC) results in persistent or recurrent anal SCC. Treatment with salvage abdominoperineal resection (APR) can potentially achieve cure. The aims of this study are to analyze oncological and surgical outcomes of our 30-year experience with salvage APR for anal SCC after failed CRT and identify prognostic factors for overall survival (OS).MethodsAll consecutive patients who underwent salvage APR between 1990 and 2016 for histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 37 publications
1
11
0
3
Order By: Relevance
“…This study confirmed that salvage APR for either persistent or recurrent anal SCC, after failed initial treatment with CRT, can achieve long-term survival and durable local control 2. An overall 5-year survival rate of 41.6% was achieved, and the 5-year local recurrence rate was 44.7%.…”
Section: Presentsupporting
confidence: 75%
“…This study confirmed that salvage APR for either persistent or recurrent anal SCC, after failed initial treatment with CRT, can achieve long-term survival and durable local control 2. An overall 5-year survival rate of 41.6% was achieved, and the 5-year local recurrence rate was 44.7%.…”
Section: Presentsupporting
confidence: 75%
“…In their 26-year study in 2018, Hagemans, et al [6] conducted a study which included 47 patients and reported better results compared to the other published studies. The R0 rate was higher (80.9%) and the 5-year survival rate was 41.6% (against 35.2% in our study).…”
Section: Discussionmentioning
confidence: 97%
“…Efforts have been made to identify differences in outcome comparing persistent vs. recurrent disease [ 128 ]. Although some studies demonstrate no survival difference among patients who receive salvage APR for persistent vs. recurrent disease [ 135 , 137 , 138 ], others suggest that persistent disease or early recurrence may be associated with worse outcomes, possibly due to more aggressive tumor biology in persistent disease or early recurrence [ 132 , 133 , 139 , 140 ]. Innovations in surgical technique for APR may improve outcomes [ 131 ].…”
Section: Treatment Of Persistent/recurrent Diseasementioning
confidence: 99%